Effect of Nd: YAG laser on the solvent evaporation of adhesive systems - Batista, Graziela Ribeiro [UNESP]; Barcellos, Daphne Camara [UNESP]; Gomes Torres, Carlos Rocha [UNESP]; Damiao, Alvaro Jose; Moises de Oliveira, Hueder Paulo; Paiva Goncalves, Sergio Eduardo de [UNESP] (Quintessence Publishing Co Inc, 2015)
Objective: This study evaluated the influence of Nd: YAG laser on the evaporation degree (ED) of the solvent components in total-etch and self-etch adhesives. Materials and methods: The ED of Gluma Comfort Bond (Heraeus-Kulzer) one-step self-etch adhesive, and Adper Single Bond 2 (3M ESPE), and XP Bond (Dentsply) total-etch adhesives was determined by weight alterations using two techniques: Control -spontaneous evaporation of the solvent for 5 min; Experimental -Nd: YAG laser irradiation for 1 min, followed by spontaneous evaporation for 4 min. The weight loss due to evaporation of the volatile components was measured at baseline and after 10 s, 20 s, 30 s, 40 s, 50 s, 60 s, 70 s, 80 s, 90 s, 100 s, 110 s, 2 min, 3 min, 4 min, and 5 min. Results: Evaporation of solvent components significantly increased with Nd: YAG laser irradiation for all adhesives investigated. Gluma Comfort Bond showed significantly higher evaporation of solvent components than Adper Single Bond 2 and XP Bond. All the adhesives lost weight quickly during the first min of Nd: YAG laser irradiation. Conclusion: The application of Nd: YAG laser on adhesives before light curing had a significant effect on the evaporation of the solvent components, and the ED of Gluma Comfort Bond onestep self-etch adhesive was significantly higher than with Adper Single Bond 2 and XP Bond total-etch adhesives. Clinical relevance: The use of the Nd: YAG laser on the uncured adhesive technique can promote a greater ED of solvents, optimizing the longevity of the adhesive restorations.